Symbolic Convergence in A Social Movement: A Case of â€œPengumpulan Satu Juta Ktpâ€ by Teman Ahok - Angeline, Mia (Bina Nusantara University, 2016)
Internet plays an important role in modern social movements. One of the modern social movements succeeded in Jakarta was initiated by Teman Ahok named